Examination of The Rulings on Marriage with the Ahl-u-al Kitab from the Perspective of Islam - BANAWRI, Abdul Mutalib (Farah Research and Scientific Journal, 2025)
The divine religion of Islam has established various rulings at different stages for the continuity of human life and the survival of their generations. Some of these rulings pertain to the individual life of a person, while others relate to their social life. Among these is the important issue of family matters, which constitutes a significant part of human life and is considered relatively more important than other aspects; this is because its effects are not limited to the individual’s life but also extend to others. One of the important issues in this area is the marriage with the Ahl-u-al Kitab, which is universally accepted as permissible based on the Quranic text. However, the Ahl-u-al Kitab during the time of the revelation of the Quran differ in many aspects, such as beliefs, from the contemporary Ahl-u-al Kitab. This research has been conducted using a descriptive-analytical method, and to substantiate the findings, verses from the Holy Quran, Prophetic traditions, and reputable jurisprudential texts have been utilized regarding the ruling on marriage with women from the Ahl-u-al Kitab. The most important results of this research indicate that the marriage of a Muslim woman to men from the Ahl-u-al Kitab and other non-believers is not permissible according to Islamic law. However, the marriage of a Muslim man to a woman from the Ahl-u-al Kitab is a matter of dispute among esteemed scholars, with the very permissibility being established from religious texts, but the ruling and its forms have changed over time. Additionally, in the case of such a marriage, all ceremonies must be conducted in accordance with Islamic regulations.